Analysis of PT Fokus KuAnalysis of PT Fokus Kualitas Utama Digital Marketing Strategy to Increase Client Attraction alitas Utama Digital Marketing Strategy to Increase Client Attraction - Amelia, Novi; Wardani, Nuruni Ika Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the implementation of digital marketing strategies by PT. Primary Quality Focus in increasing client attraction. Qualitative descriptive methods with the AIDA (Attention, Interest, Desire, Action) analysis model are used to expand digital marketing strategies. Focus on Attention emphasizes quality, providing a superior experience, high-quality service, and engaging digital content. On Interests, the company drives interaction and engagement through quizzes, polls, and periodic content, building interest and two-way relationships. Desire is stimulated through content that highlights service excellence and client testimonials. The Action stage encourages the audience to utilize the service after going through the Attention, Interest and Desire process. The results of this research indicate that the digital marketing strategy implemented by PT. The Main Quality Focus provides a significant positive impact on business growth, so that it is able to attract the attention of clients every year. However, companies need to optimize consistency in LinkIn and Websites in order to get more effective improvements to increase the attractiveness of service company clients in the digital era.